أنموذجا :- وزارة الحسن بن مخلد بن الجراح في خلافة المعتمد على الله (256-279هـ/869-892م) أنموذجا :- الكاتب أبي العباس احمد بن محمد بن الفرات في خلافة المعتضد بالله (279-289هـ/892-9تدابير الإدارة المالية للدولة العباسية - عبد الرزاق محمود الجيلاوي, ندى (Al-Adab Journal, 2018)
By delving into the details of our search season it is marked by the " financial management of the Abbasid state measures" in our selection of the administrative and financial models for some of the ministers and the writers and found it to these characters of positive and negative role of administrative , financial and importance during the period of their work in government offices and ministries . These characters had practiced that belong to the families of its important place and these families: Al jrah family and Al forat family , which took an important and powerful positions at the same time requires the ability of administrative , financial and efficiency for the management of the affairs of state in the fiscal side as well as characterized by the families of experience and expertise in this aspect especially bureaucracy Management . There were different dimensions and limits of the minister the authority depending on personal caliphs and political conditions of the Abbasid state , we have explained in our political conditions of each successor within a period of characters who take them and had a lot of Ministers of great influence and power until the minister he became the supreme authority of the affairs of the state and most of the caliphs delegate their ministers in the rule of the state ,the minister was masterminding the rule and display the armies and the provision of funds and oversee the collection and conduct succession duties and the administration of justice and supervision of the management . We have observed through our search these ministers and writers have been subjected to removal from office , whether financial or personal reasons , such as hostility and hatred of men and attendants of the caliphs, and also subjected to imprisonment and confiscation of their movable and immovable property , or be the cause of dismissal them for the intervention of women and their influence in state policy such as the lady Muqtadir's mother. As well as the position of the ministry to be noticed in the case of strength or weakness of character by caliph and its impact on its employees and their own men . Because of the instability of the ministers in their posts and their exposure to isolate and confiscation has been characterized by some ministers of manipulating and taking money from the state treasury and the large expenses and extravagance in several areas , whether of them positive or negative , and because of the Abbasid state's political conditions and the deterioration of their conditions was the financial side its crises repeated and frequent expenditures on wars and the military and the large expenditures by the caliph who was busy lusts and leave it to minister of the reason for the occurrence of financial crises and thus to the weakness of the position of the ministry , and became minister imprisoned and humiliated and confiscation of their money and killing of familiar things even though they gave the Abbasid state of great services in the creation and the development of bureaucracy and thus to the recovery of the financial side of the state through the administrative and financial recruited to their experience , skill and efficiency in these aspects.